Development of Augmented Reality-Based Scansmart Card Media to Improve Elementary Students’ Understanding of Photosynthesis in Support of SDG 4 (Quality Education) - Yulia Salsa Billa; Arina Restian (Postgraduate, University of Mataram, 2026)
This study aimed to develop and evaluate the effectiveness of Augmented Reality (AR)-based Scansmart Card learning media to improve fourth-grade students’ understanding of photosynthesis in elementary schools, in line with Sustainable Development Goal 4 (Quality Education). The research employed a Research and Development (R&D) approach using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. The developed media integrates printed cards with AR features accessed through the Assemblr Edu application, presenting interactive 3D visualizations, audio explanations, and quizzes related to photosynthesis concepts. Product validity was assessed by material and media experts, resulting in validity scores of 92 and 95%, respectively, which were categorized as highly valid. Limited field trials were conducted with 30 fourth-grade students at SDN Tlekung 02 Batu using a one-group pretest–posttest design. Data analysis included normality testing using the Shapiro–Wilk test, paired sample t-test, and N-gain analysis. The results indicated that the data were normally distributed and showed a significant difference between pre-test and post-test scores (t = 6.87; p < 0.05). The average N-gain score was 0.63, categorized as moderate, indicating effective learning improvement. These findings demonstrate that the AR-based Scansmart Card media is valid, feasible, and effective in enhancing students’ understanding of photosynthesis and supporting the improvement of elementary science learning quality.